Indirect effects of calcium and phosphate ions releasing from Polycaprolactone – Biphasic Calcium Phosphate scaffolds on osteoblastic activities - Luntheng, Thunmaruk; Thuaksuban, Nuttawut; Monmaturapoj, Naruporn (Asian Health, Science and Technology Reports, 2016)
Objective: To evaluate indirect effects of calcium and phosphate ions releasing from the Polycaprolactone (PCL) – Biphasic Calcium Phosphate (BCP) scaffolds fabricated by modified Melt Stretching and Multilayer Deposition (mMSMD) technique on proliferation and differentiation of osteoblasts. Materials and Methods: The scaffolds were prepared as group A; PCL-20%BCP and group B; PCL-30%BCP (%wt). Amount of calcium and phosphate ions releasing from the scaffolds of both groups which immersed in culture medium (α-MEM) were assessed over 30 days. The effects of those ions on proliferation and differentiation of the osteoblasts cell lines (MC3T3-E1) were assessed using ELISA after culturing the cells in the medium with the immersed scaffolds over 21 days. The medium without scaffolds was used as the control group for all experiments. Results: The release of calcium and phosphate ions from both groups remarkably increased on day 7 (p<0.05) and then stable since day 14. No difference of their releasing profiles between the groups was detected (p>0.05). The accumulative increase of those ions in both groups corresponded to their profiles of the cell proliferation and the levels of osteocalcin (OCN), but, the relationship was not found with the profiles of alkaline phosphatase (ALP). The ALP activity of group A increased with time and it was significantly higher than those of group B and the control group on day 21 (p<0.05). In addition, the OCN levels of group A were higher than those of the other groups over the observation period. Conclusion: PCL-BCP mMSMD scaffolds can sustain the releases of calcium and phosphate ions over the period of bone formation which are essential for supporting proliferation and differentiation of the osteoblasts. Those ions released from the PCL-20%BCP scaffolds would support the early and late phase of osteoblastic differentiation better than the PCL-30%BCP scaffolds, whereas, their effects on the cell proliferation are not different.